Neurofilament light chain and total tau in the differential diagnosis and prognostic evaluation of acute and chronic inflammatory polyneuropathies. (20th June 2022) - Kmezic, Ivan; Samuelsson, Kristin; Finn, Anja; Upate, Zane; Blennow, Kaj; Zetterberg, Henrik; Press, Rayomand
Abstract: Background and Purpose: To investigate the diagnostic and prognostic value of axonal injury biomarkers in patients with inflammatory polyneuropathies. Methods: Neurofilament light chain (NfL) and total tau (T‐tau) were measured in the cerebrospinal fluid (CSF) and plasma in 41 patients with Guillain–Barré syndrome (GBS), 32 patients with chronic inflammatory demyelinating polyneuropathy (CIDP), 10 with paraproteinemia‐related demyelinating polyneuropathy (PDN), and 8 with multifocal motor neuropathy (MMN), in comparison with 39 disease‐free controls and 59 other controls. Outcome was measured with the GBS‐disability score (GBS‐ds) or Inflammatory Neuropathy Cause and Treatment (INCAT) disability score. Results: Neurofilament light chain levels in CSF and plasma were higher in GBS, CIDP, and PDN vs. disease‐free controls. Patients with MMN had higher NfL levels in plasma vs. disease‐free controls, but lower levels in CSF and plasma vs. patients with amyotrophic lateral sclerosis (ALS). T‐tau levels in plasma were higher in GBS, CIDP, PDN, and MMN vs. all control groups. Neurofilament light chain levels in CSF and plasma in patients with GBS correlated with GBS‐ds, as higher levels were associated with inability to run after 6 and 12 months. NfL levels in CSF and plasma in CIDP did not correlate significantly with outcome. Conclusions: Acute and chronic inflammatory neuropathies are associated with an increase in levels of NfL in CSF and plasma, but NfL is validated as a prognostic biomarker only in GBS. NfL could be used in differentiating patients with MMN from ALS. T‐tau in plasma is a novel biomarker that could be used in a diagnostic assessment of patients with acute and chronic inflammatory polyneuropathies. Abstract : Acute and chronic inflammatory neuropathies are associated with an increase in levels of neurofilament light chain (NfL) in cerebrospinal fluid (CSF) and plasma, but NfL is validated as a prognostic biomarker only in Guillain–Barré syndrome. NfL in CSF and plasma could be used in differentiating patients with multifocal motor neuropathy from ALS. T‐tau in plasma is a novel biomarker that could be used in a diagnostic assessment of patients with acute and chronic inflammatory polyneuropathies.